Social Media Hate and Misinformation Campaign in the Nigeria 2023 Elections. - Jimada, Usman (IJRDO - Journal of Social Science and Humanities Research, 2023)
Abstract Social Media platforms have become safe spaces for abuse and harmful content, making them potentially hostile environments for normal users. Hate not only denies those being abused the ability to freely express themselves online, it can lead to substantial direct offline harm and violence. Online lies, misinformation, and disinformation are being weaponized by movements and individuals such as politicians for their own political, social and economic ends. Meanwhile, the platforms they use to spread their lies fail to take action. Among the popular platforms are Twitter, Facebook, Instagram, WhatsApp, Telegram and other social media outlets. According to the Center for Countering Digital Hate (CCDH) there is a growing avalanche of hate on social media especially on Twitter. However, Sacha Altay, et al have observed that “The media landscape is no longer controlled by traditional gatekeepers, and misinformation, just like any other content, is easier to publish”. (Sacha Altay, et al. 2023) In Nigeria, the advent of social media for political discourse, has given rise to social media platforms becoming the new echo chambers of misinformation, hate, insults, name calling and character assassination by political opponents in an unprecedented manner. It has made it easier to spread hateful messages and propaganda to a wider audience often with devastating consequences. As noted by Monday Ashibogwu, the use of insults during elections in Nigeria is not a new phenomenon. It has been observed in all the previous elections. (Ashibogwu, M. 2023). This study examines the use of social media for campaigns, specifically, the use of social media to spread hate and dangerous messages by political candidates contesting the Nigerian 2023 elections and their supporters. The study involves critical studies using qualitative methods and analysis. It looks at how hate speech and misinformation fuel violence in a fractured Nigeria society. There are fault lines and cleavages that have historically evolved in the Nigerian society. These fault lines have been built over time around ethno-religious differences. During elections often associated with the struggle for power these differences become overtly manifested among competing interest groups rendering the prospects for a peaceful orderly conduct of elections that is violence- free very difficult.